Awareness of silence in Hugo Mujica: from the apofhatic path to logofagia - Cheguhem, Mauricio (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
This paper aims to address the awareness of silence in Hugo Mujica from three significant ways that run through his work. When we point out the phenomenon of consciousness it is to illustrate the philosophical, theological and poetic considerations that orbit around silence in the work of the Argentine poet. With this we want to underline the arrest of the continuum of consciousness through the tool of silence. Therefore, this work aims to establish the different lines that express this silencing of consciousness or, to be more exact, the arrest of the logos that tyrannizes words. As we know, his work drinks from the apophatic way, but it is worth pointing out those directions that cross in this post-religious poetics. In this sense, it is worth highlighting a penchant for the metaphysical transcript “[i]n the word, / silence is transcended, / with silence, the word is transcended” (Mujica, 2014: 209). This philosophical inscription responds precisely to the consciousness that moves from the binomial "word and silence" to the visual configuration of silence in the body of the poem.